Collusion and the Choice of Auction: An Experimental Study - Jeroen Hinloopen; Sander Onderstal (Tinbergen Institute, 2010)
We experimentally examine the collusive properties of two commonly used auctions: the English auction (EN) and the first-price sealed-bid auction (FPSB). In theory, both tacit and overt collusion are always incentive compatible in EN while both can be incentive compatible in FPSB if the auction is repeated and bidders are patient enough. We find that the auctions do not differ in subjects' propensity to collude overtly and in the likelihood that subjects defect from a collusive agreement. Moreover, the average winning bid does not differ between the auctions unless subjects can collude overtly. Under overt collusion, stable cartels buy at a lower price in EN than in FPSB resulting in a lower average winning bid in EN.
Keywords: C92; D44; L41; 330; Collusion; English auction; First-price sealed-bid auction; Laboratory experiments; Auktionstheorie; Test